(untitled) (Journal of the College of Basic Education, 2026)
This research discussed the definition of the term "deriving branches from principles" and the "Hanafi method" in the principles of jurisprudence, and derive some contemporary branches of jurisprudence from Hanafi principles of jurisprudence. The objectives of this research were: 1- Explaining the Hanafi method in the principles of jurisprudence. 2- Explaining that the Hanafi method in the principles of jurisprudence is the best method in deriving branches of jurisprudence. 3- Deriving "branches of jurisprudence" from a specific school of thought whose principles are broad and have no exceptions, which is the Hanafi school. 4- Demonstrating the vitality and revival of Islamic jurisprudence in light of deriving contemporary or similarly contemporary branches of jurisprudence from Hanafi principles of jurisprudence. I divided this research into three sections: In the first section, I discussed the definition of the terms “takhreej, branches, and principles.” In the second section, I discussed the methods of “the principles of jurisprudence” and the details of the “Hanafi” method in “the principles of jurisprudence,” or what is called “the method of the jurists.” In the third section, I discussed examples of the principles of jurisprudence of the Hanafi school and the derivation of some contemporary jurisprudential rulings from them. The most important results of this research were the following: 1- “takhreej” is: “extracting the rulings on incidents that were not stipulated by the Imam or his companions, from their rules and principles.” 2- “The branch”: “what is built on something else and analogy is valid based on it.” 3- “The principles of jurisprudence” in the terminology of scholars denotes several meanings, including: “the preferred,” “the most prevalent,” “the rule,” and “the evidence.” 4- The Hanafi method in the principles of jurisprudence is the best method for deriving the branches of jurisprudence. 5- “The Hanafi method” is based on deriving “the principles of jurisprudence” from “the branches.” 6- There are three famous methods for the principles of jurisprudence: 1- “The Hanafi method” or “The method of the jurists”, 2- “The method of the theologians”, some call it “The Shafi’i method” and some call it “The method of the majority”. 3- “The combination of the two methods” or what some contemporaries called “The method of the later scholars”. 7- The research resulted in the graduation of some contemporary branches of jurisprudence on the principles of Hanafi jurisprudence.